PENGARUH E-SERVICE QUALITY, DAN KEPERCAYAAN ONLINE TERHADAP MINAT PEMBELIAN TOKO ONLINE DI TOKOPEDIA - nurlina nurlina (POLITEKNIK LP3I JAKARTA, 2017)
ABSTRACT The aim of this study is to determine the influences of e-service quality, and online trust on the online buying interest in Tokopedia. The study use a method of quantitative approach, due to in this study frequently presented numbers, started from the data collection, data interpretation until the result of study. Based on the result of questionnaires, it indicate the quality of Website Design, Reliability, Security, and Customer Service in Tokopedia have positive influences on the online trust. The questionnaires result also indicates that the quality of Online Trust on the Purchase Intentions in Tokopedia has a good quality which is evidenced by the Repurchase Intentions among the consumers. Keywords: e-service quality, online trust, purchase intention, tokopedia